Alkali metal carboxylic polyelectrolyte solutions with N-methylol crosslinker - GROSS; JAMES RICHARD (1976)
Water swellable absorbent articles, made from polyelectrolytes, containing free carboxylic groups, together with methods for their preparation, and a composition useful to make said articles are disclosed. The composition contains N-substituted amide compounds as the crosslinking agents. The articles are crosslinked by heating and/or removing substantially all of the water from the precursor composition.